PRODUCT INNOVATION AND DIGITAL MARKETING STRATEGIES IN ICED TEA BUSINESSES TO ATTRACT MILLENNIAL CONSUMERS - Adam Julpahmi; Muhammad Galang Arraji; Kyla Putri Ardelia; Tia Nabila; Muhammad Riyadhul Alifia; Kansha Dwi Nuraini; Alfito Anhar; Abu Naim (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this research is to study the digital marketing strategies and product innovations of iced tea companies to attract millennial generation customers. Iced tea businesses must implement effective digital marketing strategies and make product innovations to compete and meet the needs of a dynamic millennial market due to the rapid development of digital technology. This study used a quantitative approach, and preliminary data were collected through a millennial consumer survey. The results show that innovative and on-trend iced tea product innovations, as well as the use of social media, marketplaces, and online delivery platforms, have a significant influence on product appeal to millennial customers. These strategies not only make the market wider but also help customers make better choices about iced tea products.